A COLÔNIA CECÍLIA ENQUANTO ELEMENTO DE ANÁLISE PARA A COMPREENSÃO DA HISTÓRIA LOCAL A PARTIR DO JORNAL GAZETA DE PALMEIRA: UM RECORTE DOS ANOS 1990 – 1991 / 2003 / 2015 – 2016 - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
The present paper aims to perceive the relevance of the local history, specifically, Colonia Cecília’s and its guiding ideology for the construction of the historical memory of the city of Palmeira -PR. Thus, the work’s accomplishment is done through the analysis of the newspaper “Gazeta de Palmeira” in the years between 1990-1991 (period which incorporates the Colony’s centennial), 2003 (year of “Caminhos da Cecília” rural route’s formation) and also between the years 2015-2016 (period of the official inauguration of Colonia Cecília’s Memorial and the and the retake from the Colony’s route project), such years were selected for its connection to specific moments of Colonia Cecilia. Finally, through this analysis we aim to comprehend how the society of Palmeira will reframe Cecilia Colony’s experience. To achieve it, we associated de Newspaper’s view with the attitudes of the community and the State in its effort to recall and preserve such event as a fundamental formative component to understand the local history.
Keywords: Ensino de História; História do tempo presente; Cultura visual; mídias e linguagens; História local; Colônia Cecília; Anarquismo.; History teaching; Present time History; Visual culture; media and languages; Local History; Colônia Cecília; Anarchism; CNPQ::CIENCIAS HUMANAS::HISTORIA